KNOWLEDGE, ATTITUDE & PRACTICE ABOUT ORAL HYGIENE IN STUDENTS OF DISTRICT PESHAWAR - Sofia Shehzad; Afaq Farooq; Zainab Waheed; Farooq Maqsood; Izhar Khan; Samir Khan Kabir (Pakistan Oral & Dental Journal, 2020)
To compare the Knowledge, Attitude and Practices (KAP) about OH in school children of rural and urban area, age 10–15 year of University Town, Peshawar. The knowledge, attitude and practice regarding OH in 800 school children (10-15year) of both genders were compared between rural and urban areas. It was a comparative study with systematic random sampling. A well-arranged questionnaire was applied. A pilot study was carried out on 10% of the sample population. SPSS version 21.0 was used to analysis the data. Rural children were statistically significant about knowledge. Whereas, In Urban children there was on significant difference. In rural children, significantly boys were more aware of the benefits of toothbrush and dental flossing (p
Keywords: Comparison; Socio-economic status; Tooth brushing; Urban-Rural; Dental Diseases